The Empirical Analysis of Exchange Rate Volatility in Emerging African Economies - Kwarah, Abdullahi Murtala (Finance & Economics Review, 2022)
Purpose: The study examined the empirical nature of the exchange rates volatilities in a few selected African countries, viz. Botswana, Egypt, Morocco, and South Africa. Method: The study used quarterly data (1990q to 2018q) source from the International Monetary Fund (IMF) financial archive through the Easy-Data website. Thus conducted trend analysis which includes descriptive statistics, autoregressive conditional heteroscedasticity based on the Lagrange Multiplier (ARCH-LM) test, the EGARCH model, and the Constant Conditional Correlation GARCH (CCC-GARCH) models. Additionally, test volatility and evaluate the effect of capital flows volatility on exchange rate volatility for all the countries. Further, examine the contagious effect of the exchange rates among the countries. Result: The investigations revealed that throughout the study, Botswana experienced the highest rate of exchange rate volatility while Morocco was the least in the sample countries. Further, the series are all platykurtic, i.e. there is a reasonable level of fluctuation in the series throughout the study period. In other words, positive (appreciations) are more likely to occur in Morocco, while depreciation is more likely to occur in other countries. The trend analyses also revealed the presence of relative stability for Morocco's exchange rate, while the exchange rate of the remaining countries varied significantly. Implications: These fluctuations were acute during the period 2001-2018. In this regard, the study has concluded that the exchange rate volatility of these countries was independently determined. Thus, they can ignore monetary and fiscal policy and pursue internal goals, such as full employment, stable growth, and price stability.